Considerations on developing Education for International Understanding under the Background of Internationalization of Chinese Higher Education - Xia, Jinyuan (Social Science Learning Education Journal, 2017)
The internationalization of Chinese higher education (ICHE) is the corollary of the Opening-up policy. With âthe Belt and Roadâ Initiative, education for international understanding (EIU) plays an important role in promoting ICHE. Certain aspects should be noted: 1) To clarify the purposes of ICHE and to optimize the content system of EIU; 2) To improve the level of faculty internationalization in higher education and cultivate facultiesâ international understanding literacy; 3) To improve international exchanges and cooperation of colleges and universities against the background of internationalizationÂ Key Words: Internationalization of Chinese Higher Education, Education for International Understanding, the Belt and Road